Regulación y eficiencia de la administración pública de Michoacán. Caso secretaría de medio ambiente, cambio climático y desarrollo territorial 2018-2020 - Mendoza Madrid, Héctor Manuel (Universidad Michoacana de San Nicolás de Hidalgo, 2021)
The Public Administration is a public function that aims to preserve and progress Mexican society. Such a function, for some researchers is considered as a social science, for others, just a discipline. For the purposes of this work, public administration is a social science that has its elements, its objects and its limitations, since it is clear that, without in-depth studies on this social science, the States would not know how to improve and progress. On the other hand, public administration in Mexico should not be entrusted to a single subject, or to a single public power; It must be entrusted to each of the public powers in Mexico. Being a highly political public power, the Mexican public administration in each alternation of power is permeated with passions to preserve power, and in it the system of political spoils (Spoil System) is institutionalized. Such a system is the generating cause of administrative corruption that harms Mexico, since public institutions and their positions are distributed among the politicians who promoted a certain candidate to be President, Governor or Mayors. Finally, this public administration must be built on a career civil service or career professional service. The capacities of each and every one of the public servants must be promoted on the value of merit, the experience in the administration of public goods and services, their professional preparation and career will be the guarantee of the suitability of the position in front of the public function that will perform. All citizens deserve to hold public office through a public tender under equal conditions, as well as through a knowledge assessment.

La Administración Pública es una función pública que tiene por objeto preservar y progresar a la sociedad mexicana. Tal función, para algunos investigadores es considerada como una ciencia social, para otros, sólo una disciplina. Para efectos de este trabajo, la administración pública es una ciencia social que tiene sus elementos, sus objetos y sus limitaciones, pues es claro que, sin estudios profundos sobre esta ciencia social, los Estados no sabrían cómo perfeccionarse y progresar. Por otra parte, la administración pública en México no debe ser encomendada a un solo sujeto, ni a un solo poder público; debe estar encomendada a cada uno de los poderes públicos en México. Al ser un poder público altamente político, la administración pública mexicana en cada alternancia de poder, se ve permeada de pasiones para preservar el poder, y en ella se institucionaliza el sistema de botín político (Spoil System). Tal sistema es la causa generadora de corrupción administrativa que perjudica a México, ya que las instituciones públicas y sus cargos son repartidos entre los políticos que impulsaron a determinado candidato a ser Presidente, Gobernador, o Presidente municipal. Finalmente, esta administración pública debe erigirse sobre un servicio civil de carrera o servicio profesional de carrera. Las capacidades de todos y cada uno de los servidores públicos deben promoverse sobre el valor del mérito, la experiencia en la administración de los bienes y servicios públicos, su preparación profesional y carrera serán la garantía de la idoneidad del cargo frente a la función pública que se desempeñará. Todos los ciudadanos merecemos ocupar un cargo público mediante un concurso público en igualdad de condiciones, así como a través de una evaluación de conocimientos.
Facultad de Derecho y Ciencias Sociales. Maestría en Derecho
Keywords: info:eu-repo/classification/cti/5; FDCS-M-2021-0220; Derecho administrativo; Administración pública; Facultad discrecional; Nombramiento; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/3655